Impact of Intervention by an Antimicrobial Stewardship Team on Rational Use of Antibiotics - Ahmad Alikhani; Farhang Babamahmoodi; Alieh Khabbaz; Hamideh Abbaspour Kasgari; Sabzan Mohabbati (Research Center for Rational Use of Drugs (RCRUD), 2021)
Background: An antimicrobial stewardship program can be defined as the set of actions performed in hospitals for the rational use of antibiotics. Early conversion from intravenous to oral antibiotics plays an important role in reducing the cost of treatment, shortening the length of hospital stay, and decreasing the workload of nurses. The purpose of this study was to evaluate the impact of the implementation of antimicrobial stewardship program on duration of hospitalization and medication costs.Methods: We performed an interventional study in Razi teaching hospital. All hospitalized patients aged 18 and older who met the inclusion criteria were included. This study comprised two groups. The interventional prospective group to assess the impact of intravenous to oral antibiotic conversion, and a retrospective group in which the intervention had not been applied, used as the comparator.Results: A total of 260 cases were enrolled; 47 in the interventional group and 213 in the retrospective one. The length of hospitalization was significantly shorter in the intervention group compared to the retrospective one (5.2 vs7.9 days, p<0.001). The cost of intravenous antibiotics and total medication costs significantly decreased in the intervention group.Conclusion: Our findings suggest that conversion from intravenous to oral antibiotics is effective for reducing the length of hospital stay, antibiotic cost, and excess use of intravenous antibiotics.